2001
DOI: 10.1029/2000jc900144
|View full text |Cite
|
Sign up to set email alerts
|

Role of morphologic feedback in surf zone sandbar response

Abstract: Abstract. Several aspects of feedback mechanisms associated with surf zone sandbar response have been characterized using bathymetric surveys, sampled approximately monthly over a 16-year period at the Army Corps of Engineers' Field Research Facility (North Carolina). The measured bathymetry was alongshore averaged and modeled by the superposition of two Gaussian-shaped sandbars on an underlying planar slope. A third, half-Gaussian-shaped bar represented steepening at the shoreline. The rms error between the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 41 publications
4
63
0
Order By: Relevance
“…Cross-shore bar migration has been described at different time scales. At short time scales, bars undergo offshore migration during high-energy wave conditions, when the wave height-water depth ratio is large and the undertow current (nearbottom, breaking wave-driven steady flow) is dominant (e.g., Plant et al, 2001). Onshore bar migration occurs as the wave height-water depth ratio decreases, during intermediate wave conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-shore bar migration has been described at different time scales. At short time scales, bars undergo offshore migration during high-energy wave conditions, when the wave height-water depth ratio is large and the undertow current (nearbottom, breaking wave-driven steady flow) is dominant (e.g., Plant et al, 2001). Onshore bar migration occurs as the wave height-water depth ratio decreases, during intermediate wave conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that these nearshore bars at Duck interact with driving forces to generate nonlinear feedback mechanisms (Lippmann and Holman, 1990;Lippmann et al, 1993;Plant et al 2001). The stronger nonlinearity identified in this study for periods of increased beach volume is thus inferred to be associated with these nonlinear bar mechanisms.…”
Section: Discussion Of Model Resultsmentioning
confidence: 50%
“…storm waves and/or surge effects); more intricate nonlinear feedback mechanisms (e.g. "destabilising" feedback effects that result in the decay of nearshore bars under continuous nonbreaking conditions (Plant et al, 2001)); and limitations imposed by the differences in the sampling frequencies of the beach profile and wave data. It should also be recalled that the state-dependent nonlinearity investigated here is associated only with P (i.e.…”
Section: Discussion Of Model Resultsmentioning
confidence: 99%
See 2 more Smart Citations